Assessing social accountability perspectives among Syrian medical students: a cross-sectional study - Sarya Swed; Hidar Alibrahim; Haidara Bohsas; Mohamad Nour Nasif; Yasmeen Abouainain; Yazan Khair Eldien Jabban; Eman Ali; Mohammad Badr Almoshantaf; Rana Alaa Alnajem; Rama Reslan; Tarek Majzoub; Bisher Sawaf; et al. (BMC Medical Education, 2023)
Abstract Background Social accountability (SA) within medical education signifies a commitment to address critical regional, societal, and national issues through educational, research, and service activities. In resource-limited regions, marginalized communities face barriers to accessing quality healthcare, and the concept of SA is often poorly understood by students. This study aims to investigate the perspectives, awareness, and comprehension of Syrian medical students regarding the concepts and principles of SA. Methods This cross-sectional online study was conducted in Syria from June 1st to July 25th, 2023, to assess the perspectives on SA among medical students enrolled in pre-clinical and clinical phases from the 3rd to the 6th year, encompassing both stream I and stream II. The questionnaire included three parts: consent and introduction, socio-demographic data, and a 12-item survey assessing social accountability. Data were analyzed using Statistical Package for the Social Sciences software version 24 (SPSS 24). Results A total of 1312 medical students (62.3% females vs. 37.7% males) participated in our analysis. Less than half of the participants (45.7%) reported that their institution had a limited social mission statement regarding the communities they serve. However, only 39.6% reported that their curriculum partially reflected the needs of the population they serve. A mere 7.5% and 6.8% of respondents indicated that their school had excellent community partners and stakeholders shaping their institution, and they learned significantly about other cultures and social circumstances in the medical context through their curriculum. About 24.1% reported that their institution required them to engage in a substantial amount of community-based learning, and 37.4% believed that their class reflected a good representation of socio-demographic characteristics of the reference population. A significant portion of the participants (44.3%) stated that their school did not encourage them to pursue generalist specialties, and 12.7% felt that their institution did not have a positive impact on the community. Among the included participants, 45.8% had some level of SA status, while 37.7% indicated good SA status. Age, gender, and the phase of study were the only sociodemographic characteristics statistically associated with SA status (p-value < 0.05). The association between the 12 items determining SA and the year of study was statistically significant for seven items (p-value < 0.05). However, adjusted logistic regression revealed no significant correlation between predicting SA status and sociodemographic factors (p-value > 0.05). Conclusion This study underscores the significant influence of clinical experience and gender on Syrian medical students’ perceptions of SA. To enhance these perceptions, medical institutions should tailor support services for different stages of training and target initiatives to engage male students.